Direct Observation of "Elongated" Conformational States in α‐Synuclein upon Liquid‐Liquid Phase Separation. Issue 46 (17th October 2022) - Ubbiali, Daniele; Fratini, Marta; Piersimoni, Lolita; Ihling, Christian H.; Kipping, Marc; Heilmann, Ingo; Iacobucci, Claudio; Sinz, Andrea
Abstract: α‐Synuclein (α‐syn) is an intrinsically disordered protein (IDP) that undergoes liquid‐liquid phase separation (LLPS), fibrillation, and forms insoluble intracellular Lewy bodies in neurons, which are the hallmark of Parkinson's Disease (PD). Neurotoxicity precedes the formation of aggregates and might be related to α‐syn LLPS. The molecular mechanisms underlying the early stages of LLPS are still elusive. To obtain structural insights into α‐syn upon LLPS, we take advantage of cross‐linking/mass spectrometry (XL–MS) and introduce an innovative approach, termed COMPASS (COMPetitive PAiring StatisticS). In this work, we show that the conformational ensemble of α‐syn shifts from a "hairpin‐like" structure towards more "elongated" conformational states upon LLPS. We obtain insights into the critical initial stages of LLPS and establish a novel mass spectrometry‐based approach that will aid to solve open questions in LLPS structural biology. Abstract : By introducing a modified cross‐linking mass spectrometry (XL–MS) approach, termed COMPASS (COMPetitive Pairing StatisticS), we unravel conformational changes of the intrinsically disordered protein α‐synuclein upon liquid‐liquid phase separation (LLPS). The conformational ensemble of α‐synuclein shifts from a "hairpin‐like" structure towards more "elongated" conformational states in liquid droplets. During this early LLPS stage, α‐synuclein remains monomeric and highly flexible.